Pengelolaan Anggaran Dana Bantuan Operasional Sekolah (BOS) Pada Masa Pandemi SMA Negeri 4 Palangka Raya - Lina Teza; Sundari, Sundari; Rohaetin, Sri; Merisa Oktaria; Alexandro, Rinto (Edunomics Journal, 2024)
Currently, the use of regular BOS funds during the pandemic makes schools have to allocate a special budget to meet the facilities and infrastructure in schools. With the emergence of Covid-19, it poses a threat to all sectors in the world. In the world of education, one of them, this is very influential in the implementation of education in Indonesia. The Government of Indonesia issued a Joint Circular Letter of the Minister of Home Affairs and the Minister of Education and Culture Number 907/6479/SJ Number 7 of 2021 concerning the Integration of Information Systems for the Management of School Operational Assistance Funds that in the context of controlling development planning, implementation, evaluation and control of national development as mandated by Presidential Regulation Number 39 of 2019 concerning One Indonesian Data and taking into account the Regulation of the Minister of Home Affairs Number 24 of 2020 concerning the Management of School Operational Assistance Funds. This study aims to describe the Management of School Operational Assistance Funds (BOS) at SMA Negeri 4 Palangka Raya during the pandemic period of the 2021 academic year. The management in question includes: (1) Planning of BOS Funds at SMA Negeri 4 Palangka Raya, (2) Implementation of the Use of Funds BOS at SMA Negeri 4 Palangka Raya, and (3) Supervision of BOS funds at SMA Negeri 4 Palangka Raya. Related to the BOS technical guidelines the principles of effectiveness, flexibility and transparency. This research is a qualitative descriptive study. The location of this research is SMA Negeri 4 Palangka Raya, Jalan Sisingamangaraja Palangkaraya, Central Kalimantan. The research subjects included school principals, treasurers, and school committee members. Data collection techniques used are through observation, interviews and documentation. The data analysis technique used is descriptive data analysis. The results showed that: the management of BOS funds at SMAN 4 Palangka Raya was in accordance with the regular 2021 BOS Technical Guidelines, namely the implementation of the principles of effectiveness and transparency during the COVID-19 pandemic in the 2021 academic year